Legal Protection for People with Mental Disorders According to the Welfare Concept of the Indonesian State - Neneng Salama; CSA TEDDY LESMANA, SH MH (West Science Law and Human Rights, 2023)
This study aims to determine the extent of legal protection for people with mental disorders according to the Indonesian state welfare concept. Legal protection is an effort to protect human rights which aims to protect the interests of every citizen in a form of service that must be provided by the government to its citizens to provide a sense of security and peace to every citizen of society. As regulated under the 1945 Constitution of the Republic of Indonesia, the state's responsibility for the protection of human rights is a very important matter. As described in Article 28I Paragraph (4) which reads: "protection, promotion, enforcement and fulfillment of Human Rights is the responsibility of the State, especially the government. Regarding the protection of the rights of people with mental disorders, the government has also passed a special regulation, namely law no. 18 of 2014 concerning Mental Health. To reinforce the government's role in fulfilling the human rights of people with mental disorders, it is included in Article 81 of Law No. 18 of 2014 concerning mental health. In addition, the government is also obliged to be responsible for placing appropriate facilities and infrastructure in fulfilling the right to life for people with mental disorders. This has been regulated in article 77 of Law no. 18 of 2014 concerning Mental Health, reads: "The Government and Regional Governments have the duty and responsibility to provide facilities and infrastructure in the implementation of Mental Health Efforts".